Roots of terrorism - Bajpai, Kanti P., 1955- (New Delhi ; New York, NY : Penguin Books, 2002)
With reference to terrorism and secessionist movements in various states in India; a study.
Includes bibliographical references (p. [179]-181).
Keywords: Terrorism -- India; Secession -- India